A Statistical Multiprobe Model for Analyzing cis and trans Genes in Genetical Genomics Experiments With Short-Oligonucleotide Arrays - Alberts, Rudi (Copyright © 2005 by the Genetics Society of America, 2005)
Short-oligonucleotide arrays typically contain multiple probes per gene. In genetical genomics applications a statistical model for the individual probe signals can help in separating “true” differential mRNA expression from “ghost” effects caused by polymorphisms, misdesigned probes, and batch effects. It can also help in detecting alternative splicing, start, or termination.